Karyotype analysis of some species of Asparagales - Mukherjee, Ashutosh; Roy, Satyesh Chandra (Current Botany, 2013)
Karyotypes of some species from different families of the order Asparagales were studied. These species varied greatly in their chromosome number and morphology. Two parameters namely total chromosome length and average chromosome length were positively correlated. UPGMA based dendrogram and Principal co-orninate analysis was also employed to assess the phylogenetic relationships among the species. The dendrogram clearly separated Ornithogalum virens from the rest of the species. Principal co-ordninate analysis, however, slightly differed from the dendrogram. This study suggests that Agapanthus should not be included in the family Alliaceae. Members of Amaryllidaceae and Hyacinthaceae also showed great variability in their karyotypes. This study shows that using proper statistical data, phylogenetic relationships can be drawn with chromosomal data.